Pagbasa sa Learning from the Filipino Diaspora: Lessons of Resistance and Critical Intervention ni E. San Juan Jr (Book Review: Learning from the Filipino Diaspora: Lessons of Resistance and Critical Intervention of E. San Juan Jr.) - Sawa-an, Mary Joy (Social Sciences and Development Review, 2022)
The collection of essays from Learning from the Filipino Diaspora: Lessons of Resistance and Critical Intervention by E. San Juan Jr. critically discusses the study of literature through a historical-materialist lens, grounded in the phenomenon of the Filipino diaspora. In this context, a reorientation of Filipino sensibilities emerges regarding each individual’s role in society, emphasizing the need to revisit their historical positioning as members of the Philippine state and community. The author’s critique is a significant contribution because it raises awareness about the conditions faced by Filipino workers abroad—from the past to the present—who leave the country to provide for their families despite the uncertainty and lack of protection against exploitation and abuse overseas. As a large portion of the Filipino population migrates to different parts of the world to work in various service roles, the work directly addresses their function as the government’s “milking cows,” given the remittances that sustain the national economy. In return, they are labeled as “modern-day heroes,” even as reports of abuse, rape, and killings continue to emerge from among their ranks.